Anger, Emotion, and Arrhythmias: from Brain to Heart - Taggart, Peter; Lambiase, Pier (Frontiers in Physiology, 2011)
Strong emotion and mental stress are now recognised as playing a significant role in severe and fatal ventricular arrhythmias. The mechanisms although incompletely understod, include central processing at the cortical and brain stem level, the autonomic nerves and the electrophysiology of the myocardium. Each of these are usually studied separately by investigators from different disciplines. However, many are regulatory processes which incorporate interactive feedforward and feedback mechanisms. In this review we consider the whole as an integrated interactive brain-heart system (brain-heart system)